Suco integral de amora (Morus nigra L.) obtido através de prensagem e despolpamento: rendimento e caracterização físico-química - Pimenta, Suzana Magda [UNESP]; Zambrano, Francy [UNESP]; Venturini Filho, Waldemar Gastoni [UNESP] (My University, 2012)
Mulberry (Morus nigra L.) is a fruit with a great potential for technological uses, which could be employed to manufacture of syrups, ice cream, candies, yoghurts, beverages, jam, etc. Only the leaf from mulberry trees is commercially used for silkworm feeding. This tree is cultivated on many agricultural environments such as small rural proprieties and settlements. Small farmers waste a great amount of their production for not knowing about mulberry technology. Thus, the objective of this work was to access extraction yield and physical-chemical properties of mulberry whole juice from ripe, green and a mixture of both by using press and depulper. Statistical analysis of results was carried by media and standard deviation calculations. 173 kg of mulberry were picked being 49.31% ripe and 50.68% green. Press delivered greater extraction yield of whole juice (80.50% to 81.60%) when compared to press (71.43% to 77.50%). Whole juice obtained from both equipments has shown the following values: soluble solids 7.45% - 12.11%, titrable acidity 0.45 – 1.23%, ratio 6.03 – 26.84, pH 3.69 – 4.35, total reducing sugar 4.05% – 9.96%, reducing sugar 3.95% - 9.15%, sucrose 0.00% - 0.04%, turbidity 221.25 NTU - >4,000 NTU. Whole juices obtained from both equipments has shown similar physical-chemical characteristics except turbidity. The authors concluded that press was the best extraction equipment due to its greater yield and whole juice quality regarding turbidity

A amora (Morus nigra L.) é uma fruta com grande potencial de aproveitamento tecnológico, podendo ser usada para fabricação de xaropes, sorvetes, doces, iogurtes, bebidas, geleias, etc. Da amoreira, apenas a folha tem sido explorada comercialmente para alimentação do bicho-da-seda. Essa planta é cultivada em diversos ambientes agrícolas, entre eles, pequenas propriedades rurais e assentamentos. Por desconhecimento dos produtores, perde-se grande parte de sua produção. Assim, o objetivo deste trabalho foi avaliar o rendimento de extração e as características físico-químicas do suco integral de amoras maduras, verdes e mistura de ambas utilizando prensa hidráulica e despolpadora vertical. A análise estatística dos resultados foi feita através do cálculo da média e do desvio padrão. Foram colhidos cerca de 173kg de amora, sendo 49,31% de maduras e 50,68% de verdes. A prensa hidráulica proporcionou maior rendimento de extração de suco integral (80,50 a 81,6%) em relação à despolpadora (71,43 a 77,50%). O suco integral obtido nos dois equipamentos apresentou valores de sólidos solúveis de 7,45 a 12,11°Brix; acidez titulável de 0,45 a 1,23g.100mL-1; Ratio de 6,03 a 26,84; pH de 3,69 a 4,35; açúcares redutores totais de 4,05 a 9,96g.100mL-1; açúcares redutores de 3,95 a 9,15g.100mL-1, sacarose de 0,00 a 0,04g.100mL-1 e turbidez de 221,25 a >4000NTU. Os sucos integrais obtidos em ambos os equipamentos apresentaram características físico-químicas similares exceto para turbidez. Concluiu-se que a prensa foi o melhor equipamento de extração, devido ao maior rendimento e qualidade do suco integral em termos de turbidez.
Mulberry (Morus nigra L.) integral juice obtained by pressing and depulpering: yield and physical-chemical characterization
Keywords: Non-alcoholic beverages; Fruits, physicalchemical analysis; Extraction yield; Extraction equipment; Bebidas não alcoólicas; Frutas, análise físico-química; Rendimento de extração; Equipamentos de extração